2017
DOI: 10.1177/0972150917692193
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Indian IPOs: An Empirical Analysis

Abstract: The present research study contributes to the extant literature on underpricing rather uniquely by addressing the under-researched linkage of corporate governance to underpricing. The originality of this effort also lies in being one of the initial efforts of exploring governance in context of initial public offering (IPO) underpricing in Indian settings. The study comprises an empirical analysis of 404 Indian IPOs studied for their board structures and ownership attributes using IPO prospectuses. Drawing supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 78 publications
1
28
0
Order By: Relevance
“…Arthurs, Hoskisson, Busenitz, and Johnson (2008) in their empirical study found a negative relation between interlocking of inside directors and underpricing suggesting that other board memberships result in acquiring of informational resources helping in mitigating information asymmetry. Handa and Singh (2017) in their study conducted for Indian IPOs found no significant relationship between interlocking of non-executive directors and underpricing of IPOs. Giving this dimension of governance a wider scope, the aim here is to capture the influence of all directors’ interlocking on pricing performance of IPOs on listing day.…”
Section: Review Of Literaturementioning
confidence: 87%
See 1 more Smart Citation
“…Arthurs, Hoskisson, Busenitz, and Johnson (2008) in their empirical study found a negative relation between interlocking of inside directors and underpricing suggesting that other board memberships result in acquiring of informational resources helping in mitigating information asymmetry. Handa and Singh (2017) in their study conducted for Indian IPOs found no significant relationship between interlocking of non-executive directors and underpricing of IPOs. Giving this dimension of governance a wider scope, the aim here is to capture the influence of all directors’ interlocking on pricing performance of IPOs on listing day.…”
Section: Review Of Literaturementioning
confidence: 87%
“…Baluja and Singh (2016) established a relation between listing delay and survival of IPO firms putting forward an explanation that more the gap between issue date and listing date, more the time investors get to gather critical information about the firm, which ultimately reflects in performance of IPOs. Handa and Singh (2017) contend that listing delay represents a degree of informed demand made by investors. Previous empirical studies have also controlled age of firm for its impact on underpricing (Reutzel & Belsito, 2015; Xu et al, 2017) as Singh, Tucker and House (1986) are of the view that older firms are relatively less affected by liability of market newness.…”
Section: Founders’ Retained Ownershipmentioning
confidence: 99%
“…Prestige signals and oversubscription ratio reputation as a signalling tool to signify their quality and reduce the cost of issuing new equity. Finally, Handa and Singh (2017) concluded that board structure is able to signal the quality of the listing firm. The current study is interested in investigating prestige signals in the Malaysian IPO market due to its high level of information asymmetry, which according to Mohd Rashid et al (2014) this high level of information asymmetry makes Malaysia the ideal candidate to examine the signalling effect.…”
mentioning
confidence: 99%
“…Initial return is the only dependent variable calculated using both closing and opening price measures. Closing price shows the change momentum of first listing day relative to offer price, but comparatively opening price measure, also known as market return, explains the opening price percentage change relative to offer price on the first day of listing (Handa & Singh, 2017;Mohd-Rashid, Abdul Rahim, & Yong, 2014). Along with closing price, opening price measurement offers additional insight in identifying appropriate determinants of initial return in Pakistan's IPO market.…”
Section: Data and Methdologymentioning
confidence: 99%